The Association between the Preoperative Prognostic Nutritional Index and the Controlling Nutritional Status Score on Tumor Stage, Chemotherapeutic Response and Overall Survival in Ovarian Cancer. (28th May 2022) - Karakaş, Sema; Demirayak, Gökhan; Önder, Ayşe Büşra; Özdemir, İsa Aykut and Comba, Cihan and Süzen Çaypınar, Sema and Yıldız, Şükrü and Avşar, Selim and Bağhaki, Sema and Yıldız, Güneş Özlem and Erdoğan, Şakir Volkan
Abstract: Objective: : This study aimed to investigate the association between preoperative prognostic nutritional index (PNI) and controlling nutritional status (CONUT) scores on the stage of ovarian cancer (OC), chemotherapeutic response, and overall survival (OS) in patients with OC. Methods: : The data of the patients who operated due to OC between January 2015 and January 2020 in a tertiary referral hospital were recorded. The patients' basic characteristics, preoperative total cholesterol, albumin, lymphocyte count, tumor markers, disease stage, grade, chemotherapeutic response, OS, and progression-free survival were recorded. The PNI and the CONUT score were calculated. Results: : The mean PNI level was considerably higher in the early-stage group than the advanced-stage group (50.02 ± 6.8 vs. 46.3 ± 7.4, p = 0.005). The AUC was 63% for the cutoff point 45.98 of PNI, whereas the AUC was 42% for the cutoff point 1.5 of CONUT score in predicting early-stage disease. The PFS and OS were significantly higher in the high PNI group than the low PNI group ( p = 0.01, p = 0.002, respectively). Conclusion: : The patients with early-stage OC had significantly higher PNI levels and lower CONUT scores in our study population.